A Disposable Immunosensor for the Detection of Salivary Mmp-8 as Biomarker of Periodontitis - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier B.V., 2024)
This work describes the development of a novel voltammetric immunosensor for the detection of salivary MMP-8 at the point-of-care. The electrochemical platform was based on a graphene (GPH) screen-printed electrode (SPE) functionalized by gold-nanospheres (AuNSs) and antibodies against MMP-8 protein (anti-MMP-8). The functionalization with anti-MMP-8 was realized by using 11-mercaptoundecanoic acid (11-MUA), thanks to its ability to give strong sulfur bonds with its –SH end, and to cross-link the –NH2 groups of the antibody molecule with the other –COOH end, using the traditional EDC-NHS method. The voltammetric sensor showed good performances with a linear range of 2.5–300 ng mL−1, a LOD value of 1.0 ± 0.1 ng mL−1 and a sensitivity of 0.05 µA mL cm−2 ng−1. Moreover, the proposed immunosensor was tested in real saliva samples, showing comparable results to those obtained with the conventional ELISA method. The biosensor was single-use and cost-effective and required a small quantity of test medium and a short preparation time, representing a very attractive biosensor for MMP-8 detection in human saliva. © 2023